Role of Fibrinolytic Enzymes in Anti-Thrombosis Therapy - Altaf, Farwa; Wu, Shourong; Kasim, Vivi (Frontiers in Molecular Biosciences, 2021)
Thrombosis, a major cause of deaths in this modern era responsible for 31% of all global deaths reported by WHO in 2017, is due to the aggregation of fibrin in blood vessels which leads to myocardial infarction or other cardiovascular diseases (CVDs). Classical agents such as anti-platelet, anti-coagulant drugs or other enzymes used for thrombosis treatment at present could leads to unwanted side effects including bleeding complication, hemorrhage and allergy. Furthermore, their high cost is a burden for patients, especially for those from low and middle-income countries. Hence, there is an urgent need to develop novel and low-cost drugs for thrombosis treatment. Fibrinolytic enzymes, including plasmin like proteins such as proteases, nattokinase, and lumbrokinase, as well as plasminogen activators such as urokinase plasminogen activator u-PA, and tissue-type plasminogen activator, could eliminate thrombi with high efficacy rate and do not have significant drawbacks by directly degrading the fibrin. Furthermore, they could be produced with high-yield and in a cost-effective manner from microorganisms as well as other sources. Hence, they have been considered as potential compounds for thrombosis therapy. Herein, we will discuss about natural mechanism of fibrinolysis and thrombus formation, the production of fibrinolytic enzymes from different sources and their application as drugs for thrombosis therapy.